Pemberdayaan Manusia di Lingkungan SMK PGRI 3 Kota Serang dalam Rangka Meningkatkan Sumber Daya Manusia - Zakky, Firzan; Sinabutar, Daniel Arnold Ferrero; Nurbintan, Rafif Prayata; Zahra, Chesya Arifia; Naibaho, Diana Stevany; Maulana, Jaka (AMERTA: Jurnal Pengabdian Kepada Masyarakat, 2025)
ABSTRACT This community service program was carried out to strengthen human empowerment in the school environment by improving students’ self-confidence and positive character as essential components of human resource development. The main problem identified was the lack of students’ awareness and understanding regarding the importance of self-confidence and positive character in supporting their learning process. The purpose of this program was to provide structured socialization aimed at enhancing students’ psychological readiness, motivation, and behavioral attitudes. The implementation method involved several stages, namely planning, preparation, coordination with the school, and direct socialization through presentations and explanations. The results of the activity showed that students gained a clearer understanding of the meaning, indicators, and importance of self-confidence and positive character, as well as ways to apply these values in daily learning. Although the activity ran effectively, several aspects still required improvement, such as the punctuality of the PKM team and the need for more communicative delivery. Overall, this program succeeded in contributing to the improvement of students’ human resource quality and provided a foundation for future empowerment activities.. Keywords: human resources, education, character, self-confidence. ABSTRAK Program pengabdian kepada masyarakat ini dilaksanakan untuk memperkuat pemberdayaan manusia di lingkungan sekolah melalui peningkatan kepercayaan diri dan karakter positif murid sebagai bagian penting dari pengembangan sumber daya manusia. Permasalahan utama yang diidentifikasi adalah masih rendahnya pemahaman murid mengenai pentingnya kepercayaan diri dan karakter positif dalam menunjang proses belajar dan pembentukan jati diri. Tujuan kegiatan ini adalah memberikan sosialisasi terstruktur agar murid memperoleh kesiapan psikologis, motivasi, serta perilaku positif yang mendukung perkembangan diri. Metode pelaksanaan meliputi tahap perencanaan, persiapan, koordinasi dengan pihak sekolah, dan pelaksanaan sosialisasi melalui penyampaian materi secara langsung. Hasil kegiatan menunjukkan bahwa murid memahami pengertian, ciri-ciri, serta pentingnya kepercayaan diri dan karakter positif, beserta cara penerapannya dalam kehidupan sekolah. Meskipun kegiatan berjalan baik, terdapat beberapa aspek yang perlu ditingkatkan seperti kedatangan tim yang harus lebih awal dan penyampaian materi yang perlu lebih komunikatif. Secara keseluruhan, kegiatan ini berhasil memberikan kontribusi terhadap peningkatan kualitas SDM murid dan menjadi dasar bagi program pemberdayaan lanjutan. Kata kunci: sumber daya manusia, pendidikan, karakter, kepercayaan diri.